Qualification and Validation of the performances of the SAR instrument on board PAZ - J. Closa-Soteras; A. Zurita; J. Sánchez; M. Labriola; A. Solana (Revista de Teledetección)
PAZ is a satellite with a highly flexible X band SAR as primary instrument. The radar is capable of generating high quality SAR images with sizes ranging from 5 km to 200 km and resolutions from 30 m for products with high coverage to values around 1m or even in the order of several cm in the case of very high resolution products. This paper describes the validation activities and the expected quality performances based on the tests performed on-ground.